Faktor Resiliensi pada Tunanetra Laki-laki Dewasa: Scooping review - Kusumaningrum, Ervia; Dewi, Nur Setiawati; Andriany, Megah (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2022)
Introduction: The prevalence of visually impaired in Indonesia has increased significantly every year. The visually impaired condition is often used by unscrupulous persons to become victims of criminal acts because of their powerlessness. Blind people need resilience to survive in the conditions experienced. There have been many studies on resilience in the blind in general, but none has specifically reviewed the visually impaired adult male. This study aims to reviewed resilience factors of visually impaired adult male.Methods: The researcher used the scoping review method to get a clear picture of resilience factors of the blind adult male. Literature search was carried out using search keywords visually impaired, resilience factors, adult male blind. The database used is Scopus, PUBMED and Google Scholar. Articles inclusion criteria are articles reviewed of publication in the last 10 years (2010-2020), full and specific text are available with research question about the resilience of male blind adult.Result: Based on the identification, there were 166 articles from search engines Scopus, PUBMED and Google Scholar. There were six articles that match the criteria after going through the selection process. Resilience has many factors such as the environment, family and individual. The researcher used the PEO question format (population, exposure, outcome) to find related research articles.Conclusion: Blind people have more serious challenges in building resilience, so further studies need to be done to make interventions to help build resilience for male blind adults.